2017
DOI: 10.1111/liv.13416
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term outcome of inactive and active, low viraemic HBeAg‐negative‐hepatitis B virus infection: Benign course towards HBsAg clearance

Abstract: Viraemia persistently ≤20 000-IU/mL predicts a benign clinical outcome: it was associated with transition to IC in 43% of LV-AC and to Occult HBV Infection in 20% of IC within 5-years. Nevertheless, 13.1% of individuals with low viraemia at presentation develops CHB within 1 year: 1-year HBV-DNA monitoring resulted the most accurate diagnostic approach that can be limited to at least a half of cases by the single point HBV-DNA/HBsAg quantification. The IC-diagnostic-accuracy combining HBV-DNA/total-anti-HBc/HB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

15
60
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(76 citation statements)
references
References 29 publications
(79 reference statements)
15
60
0
1
Order By: Relevance
“…These excellent outcomes after a long‐term follow‐up in patients of this “GZ new category” are encouraging, since this scenario is frequently seen in clinical practice . Olivieri et al report similar results in a recent study and defined this group with HBV‐DNA ≤20.000 IU/mL as low‐viraemic active carriers (LV‐AC) . In this report, 43.5% of LV‐AC became IC, 54.3% remained stable in this phase and only one patient (2.2%) progressed to the chronic hepatitis phase.…”
supporting
confidence: 62%
See 2 more Smart Citations
“…These excellent outcomes after a long‐term follow‐up in patients of this “GZ new category” are encouraging, since this scenario is frequently seen in clinical practice . Olivieri et al report similar results in a recent study and defined this group with HBV‐DNA ≤20.000 IU/mL as low‐viraemic active carriers (LV‐AC) . In this report, 43.5% of LV‐AC became IC, 54.3% remained stable in this phase and only one patient (2.2%) progressed to the chronic hepatitis phase.…”
supporting
confidence: 62%
“…In this report, 43.5% of LV‐AC became IC, 54.3% remained stable in this phase and only one patient (2.2%) progressed to the chronic hepatitis phase. No major liver‐related events were reported during the study …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In summary, our results show that Caucasian GZ patients present excellent outcomes after a long-term follow-up, which is in line with a recent study in HBeAg-negative patients with low replication. 37 Indeed, development of active hepatitis was rare, whereas beneficial events such as loss of HBsAg or transition into the inactive carrier state were frequent, mainly among patients infected with genotype A or D. Fluctuation of ALT and/or HBV-DNA was frequent but did not prevent a favourable outcome in the vast majority of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Even if the virological determinants underlying these kinetics are not clear, the long‐term monitoring of patients in clinical practice demonstrated that putative CIB undergoes the same outcome of true CIB, despite a lower frequency of HBsAg loss/seroconversion. This observation, which confirms recent data, is well described by the measurement of HBcrAg.…”
Section: Discussionmentioning
confidence: 99%